Characteristics and Outcomes of Heart Transplant Recipients With Coronavirus-19 Disease in a High-volume Transplant Center. Issue 3 (March 2022) - Marcondes-Braga, Fabiana G.; Murad, Ciro M.; Belfort, Deborah S.P.; Dantas, Rafael C.T.; Lira, Maria Tereza S.S.; Aragão, Carlos A.S.; Siciliano, Rinaldo F.; Mangini, Sandrigo; Seguro, Luis Fernando B.C.; Campos, Iáscara W.; Avila, Mônica S.; Bello, Mariana V.O.; et al.
Abstract : Background: Heart transplant (HT) recipients may be at higher risk of acquiring SARS-CoV-2 infection and developing critical illness. The aim of this study is to describe characteristics and outcomes of HT recipients infected by SARS-COV-2, from a high-volume transplant center. Methods: We have described data of all adult HT recipients with confirmed coronavirus disease 2019 by RT-PCR in nasopharyngeal samples from April 5, 2020, to January 5, 2021. Outcomes and follow-up were recorded until February 5, 2021. Results: Forty patients were included. Twenty-four patients (60%) were men; the median age was 53 (40–60) y old; median HT time was 34 mo; and median follow-up time 162 d. The majority needed hospitalization (83%). Immunosuppressive therapy was reduced/withdrawn in the majority of patients, except from steroids, which were maintained. Seventeen patients (42.5%) were classified as having severe disease according to the ordinal scale developed by the World Health Organization Committee. They tended to have lower absolute lymphocyte count ( P < 0.001) during follow-up when compared with patients with mild disease. Thirty-day mortality was 12.5%. However, a longer follow-up revealed increased later mortality (27.5%), with median time to death around 35 d. Bacterial nosocomial infections were a leading cause of death. Cardiac allograft rejection (10%) and ventricular dysfunction (12.5%) were also not negligible. Conclusions: Major findings of this study corroborate other cohorts' results, but it also reports significant rate of later events, suggesting that a strict midterm surveillance is advisable to HT recipients with coronavirus disease 2019.